PWE-027 Feeding Tregs for Therapeutic In Vitro Expansion – Retinoic Acid not SCFA Provides The Best Diet. (17th August 2016) - Goldberg, R; Scotta, C; Canavan, J; Irving, P; Powell, N; Sanderson, J; Lombardi, G; Lord, G
Abstract : Introduction: We have shown that Tregs expanded with rapamycin from FACS-sorted Crohn's Disease (CD) peripheral blood (PB) CD4+CD25hiCD127loCD45RA+ precursors, yield an epigenetically stable FOXP3+ cell population that is resistant to pro-inflammatory cytokine expression. 1 We will utilise this for a first in man clinical trial of Treg therapy for Crohn's disease. We wished to optimise the expression of gut homing molecules on these cells as Tregs are required at the site of action for optimal suppressive ability. Methods: Tregs were isolated from peripheral blood of CD patients and healthy controls. Retinoic acid (RA) and Rapamycin supplementation was tested in standard culture conditions as well as the addition of short chain fatty acids (SCFA). The effect of SCFA was assessed on ex-vivo expanded Tregs from CD4+CD25hiCD127loCD45RA+ precursors and induced Tregs (iTreg) from naïve T cell precursors. The expression of gut homing molecules integrin b7 and GPR15 was assessed by flow cytometry. Suppressive ability was tested in vitro using autologous effector T cells (Teff). Parametric and non-parametric data were calculated as the mean±s.d. and median (interquartile range, IQR) respectively. For comparison of parametric and non-parametric data, t- test, one- or two-way ANOVA. Results: In comparison to Rapamycin treated cells, the addition of RA significantly increased the expression of integrin beta 7 (38.7%±11.78% Rapamycin alone vs 72.26%±8.98% Rapamycin + RA p = 0.04, N = 7). RA treatment also significantly increased GPR15 expression. Cells treated with RA maintained their superior suppressive ability compared to Rapamycin treated Tregs (95.8%±3.5% vs 91.15%±10.1% p=ns; at Treg:Teff 1:1 ratio). SCFA treatment led to diminished cell viability and did not induce the expression of colonic homing molecule GPR15 in CD4+CD25hiCD127loCD45RA+ Tregs (74.4%±13.2% Rapamycin and RA treated culture vs 43.4%±17% with the addition of SCFA). Conclusion: Contrary to existing evidence in mouse, SCFA did not increase the proportion of CD4+FOXP3+ Tregs in human iTreg cultures. In conclusion, the addition of Retinoic acid not SCFA provides the optimal conditions for ex-vivo Treg expansion for cell based therapy of Crohn's disease. Reference: 1 Canavan JB, Scotta C, Vossenkamper A, Goldberg R, Elder MJ, Shoval I, et al . Developing in vitro expanded CD45RA+ regulatory T cells as an adoptive cell therapy for Crohn's disease. Gut. 2015. Disclosure of Interest: None Declared